Solestreuung auf Radwegen in Hannover. - Heberlein, Burkhard (Kirschbaum, 2018)
Seit 2013/14 wird beim Zweckverband Abfallwirtschaft Region Hannover (aha) auf Radwegen eine neue Winterdiensttechnik eingesetzt, die sich zuvor bereits in Göttingen bewährt hatte. Hierbei wird eine Räumung der Radwege mithilfe eines Winterdienstfahrzeuges mit Vorräumbesen und Solesprühverfahren durchgeführt. Göttingen greift hier auf Natursole einer naheliegenden Saline zurück. Der Salzgehalt dieser Natursole beträgt 26,5 % Natriumchlorid (NaCl). Die Fahrzeugtechnik zur Ausbringung der reinen Solestreuung unterscheidet sich deutlich von der herkömmlichen Methode: anstatt mit einem Keilpflug zur Räumung an der Fahrzeugfront und einem Verteilerteller für das Streumittel an der Heckseite des Trägerfahrzeuges wurde ein Fahrzeug mit Vorräumbesen und Solesprühbalken eingesetzt. Das Streufahrzeug wurde in den Winterdienstperioden 2013/14, 2014/15 und 2015/16 auf einer Teststrecke im Stadtgebiet List erprobt. Direkt angrenzend wurde ein herkömmliches Räumfahrzeug auf einer vergleichbaren Referenzstrecke eingesetzt.

Since 2010, the German city of Göttingen has been using a new winter service technology on cycle tracks. Politicians asked the Waste Management Authority for the Region of Hanover (aha) whether it could adopt the Göttingen model. The Göttingen model can be summed up as follows: cycle tracks are cleared using a winter service vehicle with front-mounted sweeper brushes and a brine-spreading procedure. The City of Göttingen uses a natural brine based on local saline. The salt content of this natural brine is 26.5% sodium chloride (NaCl). Because the City of Göttingen was still in the test phase, it was unable to provide any objective data about the model. However, in view of the fact that its subjective view was that the technology was convincing, the aha decided to test the procedure in a three-year trial starting in the winter of 2013/14. The vehicle technology used to spread the natural brine is very different from conventional technology: instead of having a V-blade at the front to clear snow and a distribution plate for the de-icing agent at the back of the vehicle, a vehicle with a sweeper brush at the front and a brine-spreading rail was used. The vehicle was used on a test section in the district of List in the winter service periods 2013/14, 2014/15, and 2015/16. A conventional winter service vehicle was used on a comparable section of track immediately adjacent to the one on which the Göttingen methodology was tested.
Brine-spreading on cycle tracks in the city of Hanover, Germany.
Keywords: Individualverkehr; Fahrradverkehr; Fahrradinfrastruktur; Straßenreinigung; Schnee; Winterdienst; Streuung; Streusalz; Schneeräumung